Enhancing Planar Inverted Perovskite Solar Cells with Innovative Dumbbell-Shaped HTMs: A Study of Hexabenzocoronene and Pyrene-BODIPY-Triarylamine Derivatives - Rocha Ortiz, Juan Sebastian; Wu, Jianchang; Wenzel, Jonas; Bornschlegl, Andreas; Perea, Jose Dario; Leon, Salvador; Barabash, Anastasia; Wollny, Anna-Sophie; Guldi, Dirk Michael; Zhang, Jiyun; Insuasty, Alberto; Lüer, Larry; et al. (Advanced Functional Materials, 2023)
Dumbbell-shaped systems based on PAHs-BODIPY-triarylamine hybrids TM-(01-04) are designed as novel and highly efficient hole-transporting materials for usage in planar inverted perovskite solar cells. BODIPY is employed as a bridge between the PAH units, and the effects of the conjugated π-system's covalent attachment and size are investigated. Fluorescence quenching, 3D fluorescence heat maps, and theoretical studies support energy transfer within the moieties. The systems are extremely resistant to UVC 254 nm germicidal light sources and present remarkable thermal stability at degradation temperatures exceeding 350 °C. Integrating these systems into perovskite solar cells results in outstanding power conversion efficiency (PCE), with TM-02-based devices exhibiting a PCE of 20.26%. The devices base on TM-01, TM-03, and TM-04 achieve PCE values of 16.98%, 17.58%, and 18.80%, respectively. The long-term stability of these devices is measured for 600 h, with initial efficiency retention between 94% and 86%. The TM-04-based device presents noticeable stability of 94%, better than the reference polymer PTAA with 91%. These findings highlight the exciting potential of dumbbell-shaped systems based on PAHs-BODIPY-triarylamine derivatives for next-generation photovoltaics.
CRIS-Team Scopus Importer:2023-07-21
Keywords: BODIPY; donor–acceptor; hexabenzocoronene; hole-transport materials; perovskite solar cells; π-conjugation